Corporate social responsibility, policy framing and strategic marketing: understanding the alcohol industry's use of social media in Uganda - Matthew Lesch; Su Golder; Jim McCambridge (BMC, 2024)
Abstract Background Sub-Saharan Africa is important to the future of alcohol and global health because the alcohol market there is expanding rapidly in a relatively young population. This entails a corresponding contest about whether the policy measures adopted will be shaped by scientific evidence or by industry interference in alcohol policy. This study examines how alcohol industry actors use social media. Methods Uganda was selected for study because of high levels of alcohol harm and recent alcohol policy debates. Data on the X (formerly Twitter) activity of the Ugandan companies of AB InBev and Diageo, who are the two main brewers, and the trade association including both, were collected, coded and thematically analysed. Results X is used overwhelmingly by alcohol industry actors in Uganda to promote corporate social responsibility (CSR) and alcohol policy framing content. There is little direct product marketing. The framing of policy problems and solutions, and of the actors involved in policymaking and CSR resembles that used elsewhere in the political strategies of the transnational alcohol corporations. Content which appears more emphasised in Uganda includes material on farmers, illicit trade and contribution to the economy. As elsewhere, it avoids giving attention to the policy measures which would make a difference to the levels of alcohol harms endured by Uganda. Rhetorically, X is thus used to create a parallel universe, in which the actual harms and what is known about how to reduce them are conspicuous by their absence. Conclusions The alcohol industry presents itself as indispensable to Uganda's future and appears to have developed relationships with politicians, partnerships with government, and built a coalition with farmers. This means the alcohol industry may be well positioned to oppose public health policy measures, even though their arguments lack substance and are at odds with the evidence.